Intra-laboratory validation of a human cell based in vitro angiogenesis assay for testing angiogenesis modulators - Jertta-Riina Sarkanen; Marika Mannerstrom; Hanna Vuorenpaa; Jukka eUotila; Timo Ylikomi; Timo Ylikomi; Timo Ylikomi; Tuula Heinonen (Frontiers Media S.A., 2011)
The developed standardized human cell based in vitro angiogenesis assay was intra-laboratory validated to verify that the method is reliable and relevant for routine testing of modulators of angiogenesis e.g. pharmaceuticals and industrial chemicals. This assay is based on the earlier published method but it was improved and shown to be more sensitive and rapid than the previous assay. The performance of the assay was assessed by using 6 reference chemicals, which are widely used pharmaceuticals that inhibit angiogenesis: acetyl salicylic acid, erlotinib, 2-methoxyestradiol, levamisole, thalidomide, and anti-vascular endothelial growth factor. In the intra-laboratory validation, the sensitivity of the assay (upper and lower limits of detection and linearity of response in tubule formation), batch to batch variation in tubule formation between different Master cell bank batches, and precision as well as the reliability of the assay (reproducibility and repeatability) were tested. The pre-set acceptance criteria for the intra-laboratory validation study were met. The relevance of the assay in man was investigated by comparing the effects of reference chemicals and their concentrations to the published human data. The comparison showed a good concordance, which indicates that this human cell based angiogenesis model predicts well the effects in man and has the potential to be used to supplement and/or replace of animal tests.